Impact of natural resource wealth on non-resource tax revenue mobilization in Africa: Do institutions and economic diversification matter? - (:unkn) unknown (My University, 2019)
This paper estimates the impact of natural resources rents on non-resource tax revenue mobilization. Regressions are carried out using the Panel Smooth Transition Regression model for 29 African countries over the period 1995-2012. The empirical results indicate that while natural resource rents alone have direct negative impact on non-resource tax revenue, the quality of institutions and the level of economic diversification modulate this impact. Natural resource rents enhance non-resource tax revenue collection in more diversified economies and in economies with favorable institutional environment. These findings urge African governments to allocate natural resources revenues towards diversifying the economy and strengthening the quality of institutions for enhancing non-resource tax revenue mobilization.
Keywords: African Research